A trilogy of glucocorticoid receptor actions - Tan, Chek Kun (2016)
Glucocorticoids (GCs) belong to a class of endogenous, stress-stimulated steroid hormones found in vertebrates (e.g., cortisol in humans and corticosterone in rodents); they have wide ranging physiologic effects capable of impacting metabolism, immunity, development, stress, cognition, and arousal. GCs exert their cellular effects by binding to the GC receptor (GR), one of a 48-member (in humans) nuclear receptor (NR) superfamily of ligand-activated transcription factors (1). As the first human NR to be cloned (2), GR has provided an invaluable template with which to understand how the structurally related NRs exert their complex cellular effects. Its activity also underscores the importance of small lipophilic ligands in regulating multiple biologic pathways. Like other NR family members, the GR comprises three major functional domains: (i) an N-terminal domain (NTD), which contains a constitutive activation function 1 (AF-1); (ii) a DNA-binding domain (DBD), containing two zinc finger motifs; and (iii) a C-terminal, ligand-binding domain (LBD), with its ligand-dependent AF-2 (Fig. 1A). The human and mouse GRs are encoded by a single NR3C1 gene, which product can be differentially spliced into two major isoforms, GRα and GRβ; the former is responsible for the majority of GR-mediated transcriptional activity (3). Additional variants, generated via translational regulatory mechanisms, together with posttranslational modifications (PTMs), contribute to the complexity and diversification of GR-mediated action (3, 4). These PTMs can dial up, or down, GR-mediated transcriptional activities, to confer distinct biologic functions. Relevant PTMs include phosphorylation, acetylation, methylation, ubiquitination, and SUMOylation (4). The first of these, phosphorylation, has been shown to modulate dimerization and DNA binding, coregulator interaction, and ligand-binding affinity, all of which alter transcriptional activity. A total of nine phosphorylation sites within the human GR NTD has been reported, some of which influence nuclear export and coregulator recruitment (5). Interestingly, NR SUMOylation, which involves the covalent conjugation …